Artículo 14° de la Ley de Arbitraje Peruana: Supuestos y efectos jurídicos de extensión del convenio arbitral a no signatarios, Tacna 2016 - Maclean Cuadros, Mauricio Julio (2017)
The objective was to determine the legal assumptions and effects of extension of the arbitration agreement to non-signatories, included in article 14 of the Peruvian Arbitration Law (DL1071). The type of investigation was dogmatic legal. Principales results: There is no consensus among jurists regarding the content of article 14 of the LAP.The jurisdiction Arbitration is exceptional, consecrated in the Political Constitution of 1993 and has its origin and limitations in article 139. The Peruvian Arbitration Law regulated by Legislative Decree No. 1071, has a monist character since its scope of application is national and international. Conclusion: The extension of the arbitration agreement rests on the substantial part that is the owner of the contractual interests, even if it has not signed the agreement, and is legitimately constituted in part.